2022
DOI: 10.3389/fmolb.2021.800747
|View full text |Cite
|
Sign up to set email alerts
|

Complex Involvement of the Extracellular Matrix, Immune Effect, and Lipid Metabolism in the Development of Idiopathic Pulmonary Fibrosis

Abstract: Background and objective: Idiopathic pulmonary fibrosis (IPF) is an aggressive fibrotic pulmonary disease with spatially and temporally heterogeneous alveolar lesions. There are no early diagnostic biomarkers, limiting our understanding of IPF pathogenesis.Methods: Lung tissue from surgical lung biopsy of patients with early-stage IPF (n = 7), transplant-stage IPF (n = 2), and healthy controls (n = 6) were subjected to mRNA sequencing and verified by real-time quantitative PCR (RT-qPCR), immunohistochemistry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The results of our single-cell RNA sequencing study suggested that fatty acid metabolism and immune processes are jointly involved in the early progression of IPF (44). In this study, we found that NK cells were significantly activated in the lung tissues of patients with IPF, as well as high levels of fatty acid metabolism.…”
Section: Discussionsupporting
confidence: 52%
“…The results of our single-cell RNA sequencing study suggested that fatty acid metabolism and immune processes are jointly involved in the early progression of IPF (44). In this study, we found that NK cells were significantly activated in the lung tissues of patients with IPF, as well as high levels of fatty acid metabolism.…”
Section: Discussionsupporting
confidence: 52%
“…POSTN is also named periostin, and encodes a secreted extracellular matrix protein, playing a significant role in tissue development and regeneration, including wound healing, and ventricular remodeling post myocardial infarction. An increasing number of researches revealed POSTN was significantly associated with immune www.nature.com/scientificreports/ response abnormality, inflammation, and fibrosis [27][28][29] . Similarly, our study showed the elevated POSTN expression was positively correlated with T follicular helper cells, CD8(+) T cells, and M2 macrophages while negatively correlated with resting CD4(+) memory T cells and eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…POSTN is also named periostin, and encodes a secreted extracellular matrix protein, playing a signi cant role in tissue development and regeneration, including wound healing, and ventricular remodeling post myocardial infarction. An increasing number of researches revealed POSTN was signi cantly associated with immune response abnormality, in ammation, and brosis [27][28][29] . Similarly, our study showed the elevated POSTN expression was positively correlated with T follicular helper cells, CD8(+) T cells, and M2 macrophages while negatively correlated with resting CD4(+) memory T cells and eosinophils.…”
Section: Discussionmentioning
confidence: 99%